Marital satisfaction among families living with parents-in-law: The role of marital adjustment and religiosity - Nadhirah, Ainun; Khotimah, Siti Khorriyatul (HUMANITAS published by Universitas Ahmad Dahlan., 2022)
New families living with parents-in-law are facing a challenging marital satisfaction issue. This study aimed to determine the effect of marital adjustment and religiosity on marital satisfaction simultaneously and partially. This quantitative study employs data collection techniques using marital satisfaction, marital adjustment, and religiosity scales. 90 Muslim husbands or wives who lived in their parents-in-law’s houses participated in this study. Participants' characteristics were fewer than five years of marriage, first marriage, and living in the Pamekasan Regency. Multiple linear regression was used to test hypotheses. The result shows a significant effect of marital adjustment and religiosity on marital satisfaction. While partially, the marital adjustment has a significant effect on marital satisfaction. Whereas religiosity also has a significant effect on marital satisfaction. Even though marital adjustment and religiosity affect marital satisfaction simultaneously, marital adjustment partially affects marital satisfaction higher than that of religiosity. As an implication, families living with parents-in-law need to enhance their marital adjustment to achieve marital satisfaction.